Nature-Based Motor Stimulation to Improve Gross Motor Development for Stunting Prevention in Early Childhood - Ruth Donda Eleonora; Lia Rosa Veronika Sinaga; Juneris Aritonang; Sharfina Haslin; Lidian Putri Harita (CV. Media Digital Publikasi Indonesia, 2026)
Stunting remains a major public health problem in Indonesia, with prevalence still above the WHO target. Most prevention strategies focus on nutritional interventions, while motor stimulation in early childhood is often overlooked. This study aims to analyze the effectiveness of nature-based motor stimulation in improving gross motor development and supporting stunting prevention in early childhood. The study used a quasi-experimental design with a one-group pretest–posttest approach , conducted in Bangun Sari Village, Deli Serdang Regency, involving 27 children aged 3–5 years using a total sampling technique. The intervention, in the form of structured outdoor motor stimulation activities using natural elements (soil, water, rocks, plants), was carried out three times a week for five weeks. Anthropometric data, gross motor development, and physical activity patterns were collected before and after the intervention. Analysis used a paired t-test or Wilcoxon test. The results showed a significant increase in gross motor skills (p < 0.01), physical activity (p < 0.05), and a positive trend in nutritional status. These findings demonstrate that nature-based motor stimulation is effective in enhancing gross motor development and can be a holistic strategy for preventing stunting in early childhood.